Identifikasi Spesies Lalat Buah (Drosophila sp.) melalui Pemanfaatan Umpan Buah Pisang (Musa paradisiaca) di Kecamatan Jambi Luar Kota Provinsi Jambi - Aswinda Aswinda; Dhea Febria; Fulsiana Yustia; Kharisma Dwi Khorneliana; Septia Yuliadip; Ine Tentia; Jodion Siburian (Symbiotic: Journal of Biological Education and Science, 2025)
Drosophila are small insects that are often found around ripe or rotting fruits. They have a yellow-brown body with striking red eyes. Drosophila are famous for their ability to reproduce quickly. This study aims to identify various types of Drosophila species found in various locations of Mendalo, Jambi. The methods used in the study were experimentation and observation. The trap media used ambon banana fruit (Musa paradisiaca) that had been left to rot. The research was conducted with tools used such as light microscope and LCD microscope to identify Drosophila species. The results revealed that Drosophila species that were successfully identified included D. melanogaster, D. tropicalis, and D. mercatorum, each with different morphological characteristics. From the data obtained, it can be concluded that there are three Drosophila species found in various places in Jambi Luar Kota Sub-District, Jambi.